Combination of pembrolizumab and lenvatinib is a potential treatment option for heavily pretreated recurrent and metastatic head and neck cancer. Issue 4 (31st March 2021) - Chen, Tien-Hua; Chang, Peter Mu-Hsin; Yang, Muh-Hwa
Abstract : Background: Immunotherapy has become the current standard of care for recurrent and metastatic head and neck squamous cell carcinoma (R/M HNSCC). One potential approach to improve immunotherapy efficacy is to combine pembrolizumab, an anti-PD-1 agent, with lenvatinib, a potent multikinase inhibitor. In this study, we presented our up-to-date experience with pembrolizumab/lenvatinib combination therapy in heavily pretreated R/M HNSCC. Methods: Patients who had R/M HNSCC, were ineligible for curative treatment, progressed after at least two lines of systemic treatment and had received pembrolizumab/lenvatinib combination therapy were enrolled in this study. The primary endpoint was the objective response rate. The secondary endpoints included the disease control rate, overall survival, progression-free survival, and the duration of response. Results: A total of 14 patients were enrolled in this study. All the patients had received at least two lines of systemic treatment and radiation therapy, and 71% of patients had failed previous anti-PD-1 treatment. The objective response rate of pembrolizumab/lenvatinib combination therapy was 28.6% (95% confidence interval [CI], 5.0%-52.2%). The disease control rate was 42.9% (95% CI, 17.0%-68.8%). The overall survival and progression-free survival were 6.2 months (95% CI, 2.9-9.6) and 4.6 months (95% CI, 0.05-0.9.2), respectively. Of those who had failed previous anti-PD-1 therapy, partial responses were observed in two patients. All the patients with partial responses were in the tumor proportion score <50 and combined positive score 1 to 19 groups. Conclusion: Our study provided up-to-date evidence that pembrolizumab/lenvatinib combination therapy achieved objective responses in both heavily pretreated and anti-PD-1 refractory R/M HNSCC patients. This study supported the use of pembrolizumab/lenvatinib combination therapy in R/M HNSCC patients without standard of care.